Study of haematological parameters in malaria: a prospective study - J Babariya, Manjula; kumar S. Parmar, Jitendra (Tropical Journal of Pathology and Microbiology, 2020)
Background: A blood parasites plasmodia is responsible for malaria hence there are haematological alterations in malaria. The haematological changes that have been reported to accompany malaria include anaemia, thrombocytopenia, leucocytosis and leucopenia. Methods: Total 585 smear positive malaria cases were taken and various haematological parameters were studied. Results: Out of 585 smear positive cases, P. vivax was positive in 422 (72%) cases, while P. falciparum was positive in 160 (27%) cases and mixed infection was found in 3 (1%) cases. Anaemia was seen in 420 (71.79%) cases. Normocytic normochromic blood picture was the most common type in anaemic patients 223 (38.11%). Next common finding was Normocytic hypochromic RBCs 185 (31.62%). Microcytic hypochromic RBCs found in 152 (25.98%) cases. Thrombocytopenia was seen in total 490 (83.76%) of the patients. Moderate thrombocytopenia was more common and present in 409 (70%) of patients while Severe thrombocytopenia was seen in 81 (13.84%) of cases. In falciparum malaria thrombocytopenia was present in 90% of the patients while it was present in 81.27% of the patients in vivax malaria. 129 cases (22.05%) shows leucopoenia out of which 81 (13.84%) belong to P. vivax, 45 (7.69%) belong to P. falciparum and 3 (1%) were belong to mixed infection. Total Leucocyte Count was normal in 77.95 % of the patients. Conclusions: Various haematological findings can help in early diagnosis of malaria which is essential for timely and appropriate treatment which can limit the morbidity and prevent further complications.